2020
DOI: 10.1016/j.ajpath.2020.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study Using Multiple Strains of Prion Disease in Cattle Reveals an Inverse Relationship between Incubation Time and Misfolded Prion Accumulation, Neuroinflammation, and Autophagy

Abstract: Proteinopathies result from aberrant folding and accumulation of specific proteins. Currently, there is a lack of knowledge about the factors that influence disease progression, making this a key challenge for the development of therapies for proteinopathies. Because of the similarities between transmissible spongiform encephalopathies (TSEs) and other protein misfolding diseases, TSEs can be used to understand other proteinopathies. Bovine spongiform encephalopathy (BSE) is a TSE that occurs in cattle and can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 72 publications
(54 reference statements)
1
18
0
Order By: Relevance
“…The differences observed between the two forms of scrapie could reflect differences in the toxicity of both prions, as atypical scrapie displays longer incubation periods than the classical form. In line with these findings, a recent study reported that strain-dependent incubation period is negatively correlated with PrP Sc deposition and neuroinflammation, but positively with autophagy (Mammadova et al, 2020). Retinas from cattle inoculated with classical BSE displayed an upregulation of autophagy indicated by the increase of LC3-II, whereas those inoculated with atypical BSE displayed a downregulation, which suggests that autophagic dysfunction contributes to increased PrP Sc accumulation in atypical BSE, leading to greater neuroinflammation, shorter incubation periods and, therefore, an accelerated disease progression when compared to classical BSE.…”
Section: Molecule Regulation Prion Disease Model References P62 Upsupporting
confidence: 62%
“…The differences observed between the two forms of scrapie could reflect differences in the toxicity of both prions, as atypical scrapie displays longer incubation periods than the classical form. In line with these findings, a recent study reported that strain-dependent incubation period is negatively correlated with PrP Sc deposition and neuroinflammation, but positively with autophagy (Mammadova et al, 2020). Retinas from cattle inoculated with classical BSE displayed an upregulation of autophagy indicated by the increase of LC3-II, whereas those inoculated with atypical BSE displayed a downregulation, which suggests that autophagic dysfunction contributes to increased PrP Sc accumulation in atypical BSE, leading to greater neuroinflammation, shorter incubation periods and, therefore, an accelerated disease progression when compared to classical BSE.…”
Section: Molecule Regulation Prion Disease Model References P62 Upsupporting
confidence: 62%
“…Relative to other species with prion diseases, cattle with BSE generally have little to no lymphoid distribution of PrP Sc , except for tonsils and transiently in Peyer's patches [50,51]. Though atypical strains appear in older animals, experimental intracranial transmission of atypical strains of BSE results in a much shorter incubation time compared to C-BSE [52,53]. Unlike other species, polymorphisms in the PRNP gene of cattle are extremely rare, thus disease susceptibility and incubation time is not affected by an animal's genotype [53].…”
Section: Bovine Spongiform Encephalopathymentioning
confidence: 99%
“…As such, the retina in cases of prion disease is also being studied [100,109]. It has been demonstrated that PrP Sc accumulates in the retina of cattle with BSE [47,52,53,100,[110][111][112], sheep and goats with scrapie [58,109,111,[113][114][115][116][117][118][119][120][121][122][123][124], cervids with CWD [121,[125][126][127][128][129][130][131][132][133], and humans with prion diseases [134][135][136][137].…”
Section: Retinal Ganglion Cellsmentioning
confidence: 99%
See 2 more Smart Citations